Meteor head echo polarization at 930 MHz studied with the EISCAT UHF HPLA radar - Wannberg, G.; Westman, A.; Pellinen-Wannberg, A. (Annales Geophysicae, 2011)
The polarization characteristics of 930-MHz meteor head echoes have been studied for the first time, using data obtained in a series of radar measurements carried out with the tristatic EISCAT UHF high power, large aperture (HPLA) radar system in October 2009. An analysis of 44 tri-static head echo events shows that the polarization of the echo signal recorded by the Kiruna receiver often fluctuates strongly on time scales of tens of microseconds, illustrating that the scattering process is essentially stochastic. On longer timescales (> milliseconds), more than 90 % of the recorded events show an average polarization signature that is independent of meteor direction of arrival and echo strength and equal to that of an incoherent-scatter return from underdense plasma filling the tristatic observation volume. This shows that the head echo plasma targets scatter isotropically, which in turn implies that they are much smaller than the 33-cm wavelength and close to spherically symmetric, in very good agreement with results from a previous EISCAT UHF study of the head echo RCS/meteor angle-of-incidence relationship. Significant polarization is present in only three events with unique target trajectories. These all show a larger effective target cross section transverse to the trajectory than parallel to it. We propose that the observed polarization may be a signature of a transverse charge separation plasma resonance in the region immediately behind the meteor head, similar to the resonance effects previously discussed in connection with meteor trail echoes by Herlofson, Billam and Browne, Jones and Jones and others.